Symposium 2: The role of teachers in professional studies and perspectives on networked learning - Cendon, Eva (Proceedings of the International Conference on Networked Learning, 2018)
This paper examines the roles of teachers in higher education with regard to networked learning. Based on the assumption that learning is a social endeavour that incorporates both individual learning and learning with and from others, learning requires a relation between the learner and the subject, a relation between the learner and others, and last but not least a relation between the learner and the teacher. While lots of attention has been put on learning not least from a social constructive view on how to establish a learning environment in order to support learning processes, the central role of teachers in this process has often been neglected. Starting from this perspective the paper presents findings from an explorative qualitative study on the roles of teachers in learning processes in the context of higher education, more precisely in professional studies in Germany. Based on the study’s findings future perspectives for the roles of teachers in higher education with regard to networked learning are outlined.